HUBUNGAN TINGKAT PENDIDIKAN IBU DENGAN CARA MENYUSUI YANG BENAR DI BPS IBU YUNI LESPADANGAN MOJOKERTO - SUDARSIH, SRI (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2010)
The way of good breast fed is the important for mother who breast feeds her baby. Because it influences to fluency and expending ASI until the baby doesn’t get it exclusively. The factors make lactation down is surrounded about knowledge, educational, proper behavior and the values of conviction. So, the reasons are explained before that researcher gets research about the relationship about level education of mother breast feeding and her right way of breast feed. The purpose is to know the relationship about level education and the right way breast feed. The desighn of this research is used by analitic with correlation study, its population in this reasearch are mother of childbirth physiologically who breast feeds by amount of 33 respondents. Getting sampling is done by accidental sampling and collecting data is got by observation, then the data are collected by examination by chi-square with level 0.05. From examination of chi-square is got X2 adding (6.50) > X2 table (3.84) so, H1 accepted that means the level education for mother that makes good attitude and the next, there is giving ASI with good breast feeding.Key words: education, mother who breast feeds.